Enhancing Firm Value: Exploring the Nexus of Social Responsibility, Dividend Policy, and Profitability: Optimasi Nilai Perusahaan: Eksplorasi Hubungan Tanggung Jawab Sosial, Kebijakan Dividen, dan Profitabilitas - Choiri, Ika; Fitriyah, Hadiah (Universitas Muhammadiyah Sidoarjo, 2024)
This research delves into the intricate relationship between corporate social responsibility (CSR), dividend policy, profitability, and company value within the consumer goods sector of the Indonesia Stock Exchange from 2019 to 2022. Employing a purposive sampling method, 27 companies were selected for analysis using SPSS techniques. The study reveals a noteworthy finding: while dividend policy shows no significant impact, both CSR and profitability significantly influence company value. This underscores the critical importance of integrating social responsibility practices into corporate strategies, as they not only contribute to enhanced company value but also augment profitability. These findings have substantial implications for businesses, emphasizing the imperative of embracing CSR initiatives as integral components of sustainable corporate development strategies. Highlights : CSR integration: Study underscores the importance of integrating CSR practices into corporate strategies. Profitability impact: Profitability significantly influences company value in the consumer goods sector. Limited impact of dividend policy: Dividend policy shows no significant impact on company value in the Indonesian context. Keywords: CSR, dividend policy, profitability, company value, consumer goods sector